Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

how do I solve the function:
Given f(x) = 5x − 7 and
g(x) = 11x − 1, solve for (g - f)(x).


Sagot :

Answer:

6x + 6    

Step-by-step explanation:  

[tex](g-f)(x)[/tex] is equal to [tex]g(x)-f(x)[/tex]. So, the question is asking for you to subtract the given functions in that order. We know that [tex]g(x) = 11x-1[/tex] and [tex]f(x) = 5x-7[/tex]. Thus, take the values of those functions and subtract them:

[tex]g(x) - f(x)\\= (11x-1)-(5x-7)\\= 11x-1-5x+7\\=6x+6[/tex]

Thus, the answer is 6x + 6.